Employing the artistic style of potter Qasim Nayef (In the productions of students of the Department of Art Education) (Journal of the College of Basic Education, 2022)
The research was concerned with studying the artistic style of the potter Qassim Nayef, whose work was characterized by a new character, whether in form or content, depending on the raw technique and the vocabulary of his work that was inspired by nature and heritage. Employing the artistic style of the potter Qassem Nayef in the productions of the students of the Department of Art Education, the third stage.The second chapter dealt with four sections, the first was contemporary Iraqi ceramics, and the second was style and stylistics. The third section dealt with the artistic elements in the ceramic artistic composition, and the fourth section dealt with the analysis of the artist’s samples, Qassem Nayef. Artistic (30) students.